Potential inhibitors of SARS-cov-2 RNA dependent RNA polymerase protein: molecular docking, molecular dynamics simulations and MM-PBSA analyses. Issue 1 (2nd January 2022) - Elkarhat, Zouhair; Charoute, Hicham; Elkhattabi, Lamiae; Barakat, Abdelhamid; Rouba, Hassan
Abstract: The SARS-cov-2 RNA dependent RNA polymerase (nsp12) is a crucial viral enzyme that catalyzes the replication of RNA from RNA templates. The fixation of some ligands in the active site may alter the viral life cycle. The aim of the present study is to identify the conservation level of nsp12 motifs (A–G), using consurf server, and discover their interactions with rifabutin, rifampicin, rifapentin, sorangicin A, streptolydigin, myxopyronin B, VXR and VRX using AutoDockTools-1.5.6, Gromacs 2018.2 and g-mmpbsa. Thus, the most of amino acids residues located in nsp12 protein Motifs (A–G) were predicted as highly conserved. The binding energies of streptolydigin, VXR, rifabutin, rifapentine, VRX, sorangicin A, myxopyronin B and rifampicin with nsp12 protein are −8.11, −8.23, −7.14, −6.94, −6.55, −5.46, −5.33 and −5.26 kcal/mol, respectively. In the other hand, the binding energies of ligand in the same order with nsp7–nsp8–nsp12 complex are −7.23, −7.08, −7.21, −7, −6.59, −8.73, −5.52, −5.87 kcal/mol, respectively. All ligands interact with at least two nsp12 motifs. The molecular dynamics simulation of nsp12–streptolydigin and nsp12–VXR complexes shows that these two complexes are stable and the number of hydrogen bonds as a function of time, after 30 ns of simulation, varies between 0 and 6 for nsp12–streptolydigin complex and between 0 and 4 for nsp12–VXR complex. The average of free binding energies obtained using g_mmpbsa, after 30 ns of simulation, is −191.982 Kj/mol for nsp12–streptolydigin complex and −153.583 Kj/mol for nsp12-VXR complex. Our results suggest that these ligands may be used as inhibitors of SARS-cov-2 nsp12 protein. Communicated by Ramaswamy H. Sarma